IRF4 in multiple myeloma—Biology, disease and therapeutic target. (September 2018) - Agnarelli, Alessandro; Chevassut, Tim; Mancini, Erika J.
Graphical abstract: Highlights: Multiple myeloma is an incurable cancer characterized by the clonal proliferation plasma cells. IRF4 is the master regulator of an aberrant gene expression programme in multiple myeloma. Targeting IRF4 is an attractive and broadly applicable therapeutic option for multiple myeloma. Future work might focus on the development of small molecule inhibitors of IRF4. Abstract: Multiple Myeloma (MM) is an incurable hematologic malignancy characterized by abnormal proliferation of plasma cells. Interferon Regulatory Factor 4 (IRF4), a member of the interferon regulatory family of transcription factors, is central to the genesis of MM. IRF4 is highly expressed in B cells and plasma cells where it plays essential roles in controlling B cell to plasma cell differentiation and immunoglobulin class switching. Overexpression of IRF4 is found in MM patients' derived cells, often as a result of activating mutations or translocations, where it is required for their survival. In this review, we first describe the roles of IRF4 in B cells and plasma cells and then analyse the subversion of the IRF4 transcriptional network in MM. Moreover, we discuss current therapies for MM as well as direct targeting of IRF4 as a potential new therapeutic strategy.